Employment 'Miracles' A Critical Comparison of the Dutch, Scandinavian, Swiss, Australian and Irish Cases versus Germany and the US - Schwartz, Herman; Becker, Uwe (Changing Welfare States, 2005)
Why did some economies experience a boom in the 1990s? Employment 'Miracles' comparatively analyses select miracle economies. The contributors to the volume critically analyze how the small size and institutional structure of seven countries like the Netherlands, Denmark and Ireland accounted for their success and status as economic models. Comparisons with the American and German markets reveal how differing policies - liberal versus corporatist/social democratic - determine job growth and levels of income inequality and poverty. The book also stresses the explanatory relevance of lucky circumstances such as the housing price bubble. Employment 'Miracles' is an important resource for political scientists and economists in their study of employment development.